Integrating the language laboratory with a communicative approach to teaching English second language to Afrikaans-spreakers at senior secondary and tertiary levels in South Africa : an exploratory study - Swartz, Johannes Jurgens (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1985.